2023
DOI: 10.3390/jcm12123874
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Gut: A Systematic Review of Oral Manifestations in Celiac Disease

Abstract: Background: Celiac disease (CD) is a chronic immune-mediated gluten-sensitive enteropathy, affecting about 1% of the population. The most common symptoms include diarrhea, abdominal pain, weight loss, and malabsorption. Extra-intestinal symptoms include oral manifestations. This systematic review aims to catalog and characterize oral manifestations in patients with CD. Methods: a systematic literature review among different search engines using PICOS criteria has been performed. The studies included used the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
(182 reference statements)
0
3
0
Order By: Relevance
“…The literature reports that iron, folic acid and vitamin B12 deficiencies due to intestinal malabsorption in CD may be a possible cause of oral symptoms 14 . Lucchese et al 17 . reported that hematins deficiencies such as iron, folates or vitamin B12 appear to play a role in the pathogenesis of RAS while up to 25% of angular cheilitis is supposed to be caused by iron or vitamin B deficiency 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature reports that iron, folic acid and vitamin B12 deficiencies due to intestinal malabsorption in CD may be a possible cause of oral symptoms 14 . Lucchese et al 17 . reported that hematins deficiencies such as iron, folates or vitamin B12 appear to play a role in the pathogenesis of RAS while up to 25% of angular cheilitis is supposed to be caused by iron or vitamin B deficiency 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, the supplementation of these deficient microelements only marginally influenced the disease progression. Conversely, positive outcomes were reported in response to oral vitamin B12 supplementation in RAS patients, independent of their initial serum levels of this microelement 17 . The exact mechanism connecting RAS to CD has not yet been completely clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the clinical picture and the results of laboratory studies, two forms of the disease are distinguished: symptomatic (manifest) and asymptomatic (latent) [27,35,36]. The main manifestations of celiac disease are characterized by the presence of gastrointestinal symptoms (persistent diarrhea, flatulence, abdominal pain, nausea and others) and/or extraintestinal manifestations (osteoporosis, anemia, infertility, neurological symptoms and others).…”
Section: General Aspects Of Celiac Diseasementioning
confidence: 99%
“…In some cases, extra-intestinal symptoms are the only clinical manifestations of CeD that frequently remain undiagnosed. The oral cavity is likewise one of the areas of extra-intestinal signs and symptoms [5][6][7]. For example, dental complaints, particularly dental enamel defects, are well-known manifestations of CeD [8].…”
Section: Introductionmentioning
confidence: 99%